ISENTROPIC EFFICIENCY OF CENTRIFUGAL COMPRESSOR WORKING WITH REAL GAS - Jiří Oldřich (Acta Polytechnica CTU Proceedings)
The contribution deals with calculation of isentropic efficiency and also with calculation of isentropic process of real gas or gaseous mixtures. The method is based on numerical solution of basic definitional equation of isentropic process and equation of isentropic efficiency with direct implementation of real gas equation of state (EOS).